PENGARUH PENDIDIKAN THAHÃRAH TERHADAP SIKAP HIDUP SEHAT SANTRI PONDOK PESANTREN DI PEKALONGAN - Abdul Khobir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2010)
Many institutions or individuals use religious symbols or attributes, but the attitudes they display are often counterproductive to what they represent, including in matters of cleanliness. This research investigates the correlation between education on cleanliness (thaharah) and the health behavior of students in two Islamic boarding schools (pesantren), one urban and one suburban. Based on data analysis using two-way ANOVA, the research reveals that there are differences in the influence of cleanliness education between the two Islamic boarding schools and between male and female students. Furthermore, there is a significant relationship between education on cleanliness and students’ health behavior in both Islamic boarding schools when viewed from the perspective of gender.